2008
DOI: 10.1371/journal.pone.0002054
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal Fragment of MUC1 Mediates Growth of Cancer Cells

Abstract: The MUC1 protein is aberrantly expressed on many solid tumor cancers. In contrast to its apical clustering on healthy epithelial cells, it is uniformly distributed over cancer cells. However, a mechanistic link between aberrant expression and cancer has remained elusive. Herein, we report that a membrane-bound MUC1 cleavage product, that we call MUC1*, is the predominant form of the protein on cultured cancer cells and on cancerous tissues. Further, we demonstrate that transfection of a minimal fragment of MUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 35 publications
4
90
0
Order By: Relevance
“…Of the 1.3 million tumors, diagnosed in the US each year, over 60% show tumor-associated aberrant overexpression of MUC1 (Ren et al, 2004). Reaserches previously showed that ligand-induced dimerization of the extracellular domain of MUC1 induced ERK2 phosphorylation, cell proliferation and survival (Hikita et al, 2008;Mahanta et al, 2008). Thus, in trastuzumab resistant cells, MUC1 could function independently by homodimerization to increase cell growth and inhibit apoptosis, thereby countering the growth inhibitory effects of trastuzumab.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 1.3 million tumors, diagnosed in the US each year, over 60% show tumor-associated aberrant overexpression of MUC1 (Ren et al, 2004). Reaserches previously showed that ligand-induced dimerization of the extracellular domain of MUC1 induced ERK2 phosphorylation, cell proliferation and survival (Hikita et al, 2008;Mahanta et al, 2008). Thus, in trastuzumab resistant cells, MUC1 could function independently by homodimerization to increase cell growth and inhibit apoptosis, thereby countering the growth inhibitory effects of trastuzumab.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that Nm23-H1 can bind a cleaved form of Mucin1 called MUC1*, which is present on the surface of many cancer cell lines and on pluripotent stem cells (20,21). The binding of Nm23-H1 to MUC1* was reported to result in dimerization of MUC1*, and subsequent activation of the MAPK pathway to increase proliferation of the breast cancer cell line T47D (20).…”
Section: Introductionmentioning
confidence: 99%
“…This result is expected on the basis of many reports that the hMUC-1 marker is expressed on the cancer stem cells as well as the more mature epithelial neoplastic cells. [24][25][26] Clinical trials involving i.p. injection of therapy sensitization adenoviral vectors have been carried out successfully.…”
Section: Discussionmentioning
confidence: 99%
“…One such approach is immunotherapy. As the MUC-1 antigen has been found on the cancer stem cells or tumorinitiating cells as well as on the majority of the more mature cells of epithelial neoplasms, [24][25][26] we tested if the hMUC-1/ecdCD40 L VPPP vaccine when combined with the AdCMVCDIRESE1A targeted chemotherapy [5][6][7][8] could produce a decrease in the level of the CD44 +…”
Section: Cd24mentioning
confidence: 99%